The Terms of Order : Political Science and the Myth of Leadership - Robinson, Cedric J. (Book collections on Project MUSE., 2016)
"Using a variety of critical approaches in his analysis, Robinson synthesizes elements of psychoanalysis, structuralism, Marxism, classical and neoclassical political philosophy, and cultural anthropology in order to argue that Western thought on leadership is mythological rather than rational. He then presents examples of historically developed 'stateless' societies with social organizations that suggest conceptual alternatives to the ways political order has been conceived in the West."